The Impact Of Social Capital On Youth Substance Use - Unlu, Ali (2009)
Substance use, such as alcohol, cigarette, and marijuana, is a threat to the health and well-being of the youth, their families, and society as well. Government supports and implements several programs to protect youth from substance use. The aim of this study is to evaluate the impact of social capital on youth behavior and to suggest evidence-based policy interventions. Social capital refers to individual embeddedness in web of social relations and their behaviors guided by social structure. Therefore, adolescents' social interactions with their peers, parents, and community were investigated. The substance use was measured by the usage of cigarettes, alcohol, marijuana, and inhalants in the past year. The type of activities adolescents participate in, the time and type of intra-familial interactions between parents and adolescents, and the type of peer groups adolescents interact with were employed as indicators of social capital. In other words, this study focuses on the relationship between youth substance use and the impact of parents, peers, and youth activities. Moreover, the study examined not only the correlation between social capital and substance use, but also the variation in substance use among youth by age, gender, ethnicity, income level, and mobility. The data, National Survey on Drug Use and Health (2005, 2006, and 2007), was collected by the United States Department of Health and Human Service, Substance Abuse and Mental Health Services Administration Office of Applied Studies. The sample size for each year was around 17.000. Structural Equation Modeling (SEM) was used to test the hypothesized. The results of the statistical analysis supported the research hypothesis. Findings show that there is a relationship between youth substance use and social capital. All three dimensions of social capital (peer impact, family attachments, and youth activities) were found to be statistically significant. While peer influence is positively correlated with substance use, family attachment and youth activities have a negative relationship with substance use. The impact of social capital however varies by age, gender, ethnicity, mobility, and income level. The study also contributes to the social capital literature by integrating different perspectives in social capital and substance use literature. Moreover, it successfully demonstrates how social capital can be utilized as a policy and intervention tool